2013
DOI: 10.1126/science.1230969
|View full text |Cite
|
Sign up to set email alerts
|

InP Nanowire Array Solar Cells Achieving 13.8% Efficiency by Exceeding the Ray Optics Limit

Abstract: Photovoltaics based on nanowire arrays could reduce cost and materials consumption compared with planar devices but have exhibited low efficiency of light absorption and carrier collection. We fabricated a variety of millimeter-sized arrays of p-type/intrinsic/n-type (p-i-n) doped InP nanowires and found that the nanowire diameter and the length of the top n-segment were critical for cell performance. Efficiencies up to 13.8% (comparable to the record planar InP cell) were achieved by using resonant light trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
1,137
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,117 publications
(1,168 citation statements)
references
References 31 publications
15
1,137
2
4
Order By: Relevance
“…Furthermore, GaAs nanowire-based solar cells can be grown on Si, easily resulting in a dual-junction device [7]. Proof-of-concept radial p-i-n GaAs nanowire solar cells have been demonstrated in the past [8][9][10][11][12][13]. Recently, it has been shown that the achievement of high efficiencies can only be obtained after the accurate design of the individual junction, the nanowire diameter, and density so that light absorption and conversion are maximized [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GaAs nanowire-based solar cells can be grown on Si, easily resulting in a dual-junction device [7]. Proof-of-concept radial p-i-n GaAs nanowire solar cells have been demonstrated in the past [8][9][10][11][12][13]. Recently, it has been shown that the achievement of high efficiencies can only be obtained after the accurate design of the individual junction, the nanowire diameter, and density so that light absorption and conversion are maximized [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11] In addition, semiconductor NW photovoltaics (PV) are emerging as a promising platform for the next generation solar cells that require a high efficiency at costs approaching grid parity. [12][13][14][15][16][17][18][19] In particular, p/i/n core-shell NWs demonstrate electrical and optical properties distinct from conventional planar materials: radial minority carrier separation with short diffusion lengths, and enhanced light absorption resulting from the cavities' subwavelength size. [12][13][14] Recently, crystalline Si NW PVs have been successfully demonstrated, exhibiting good electrical characteristics as represented by an open-circuit voltage of ~0.5V and very low leakage current of 1 fA.…”
mentioning
confidence: 99%
“…1,2 However, the high material cost has limited commercial applications. Direct integration of GaAs nanowires on Si is a potential solution to reduce material consumption and increase cost competitiveness.…”
mentioning
confidence: 99%